FRI0223 Long term follow-up in 68 patients with primary sjÖgren's syndrome: clinical and serological features. (1st June 2001) - Ostuni, P; Sfriso, P; Grava, C; Botsios, C; Semerano, L; Todesco, S
Abstract : Background: There are few studies, regarding pSS long-term clinical course. Moreover, it has often been studied in limited groups of patients, employing different recruitment and diagnostic criteria. Objectives: During a 10 years follow-up we longitudinally studied the clinical evolution, the rate of severe complications and mortality in a large cohort of patients with pSS. Methods: We evaluated 68 consecutive outpatients with pSS according to the Fox's criteria: 67 females and 1 male, followed since January 1987 to November 2000. The patients were divided into 2 groups according to the autoantibodies pattern at the diagnosis: anti-Ro and/or La positive and anti-Ro/La negative. The prevalence of several clinical and serological abnormalities, evaluated at the beginning of the study, was compared with the prevalence observed at the end of the follow-up. Moreover, a 10 years Kaplan-Meier survival analysis was performed, considering as end points the development of lymphoproliferative disorders, death and the association death/lymphoproliferation, in order to establish how the progression of the disease might affect survival and major morbidity of pSS. Finally, we analysed whether pSS is associated with an increase of the mortality rate in comparison with the general population. Results: Eight patients from the study group died (13.2% up to 10 years of follow-up). The prevalence of arthritis in Ro and/or La positive cases was significantly higher at the beginning of the follow-up in comparison with the end of the study (p = 0.041). On the contrary, a significant higher prevalence of lymphoproliferative disorders was present in Ro and/or La positive group at the end of the follow-up (p = 0.041). We also observed significantly lower levels of C4 and significant higher IgG, IgA and ESR in the Ro and/or La positive group than in the Ro/La negative group, either at the beginning (respectively p = 0.003 p < 0.0001 p = 0.0014 p = 0.0007) or at the end (p = 0.007 p = 0.0005 p = 0.013 p < 0.0001) of the follow-up. Lymphoproliferative disorders were diagnosed in 5 patients. The development of this complication was associated with the assessment, in all the cases, of purpura, parotid swelling and low C4 levels. The 10 years-survival rate of all the pSS patients resulted 86.5% that was under the survival rate of the Italian general population (90%) (p = n.s). Conclusion: The glandular manifestations of pSS were distinctively present in the majority of the patients already at the time of the diagnosis and the serological picture remained typically constant during all the follow up. Increased IgG, IgA and ESR as well as low C4 levels were significantly prevalent in the Ro and/or La positive group. Finally, we have not found any significant increase in the mortality of pSS patients in comparison with the general population.